CHEMICAL CHARACTERIZATION AND ANTIFUNGAL ACTIVITY OF ESSENTIAL OIL OF ORANGE KINKAN (Fortunella margarita (LOUR.) SWINGLE) - MENEZES FILHO, Antonio Carlos Pereira de (2020)
Orange Kinkan (Fortunella margarita) is well known for its edible and antioxidant rich fruits. In this study, we employed Gas chromatography-mass spectrometry (GC-MS) to evaluate the antifungal potential of essential oils within both green and ripe fruits to effectively inhibit the following common plant pathogens: Sclerotinia sclerotiorum, Colletotrichum gloeosporioides, and Colletotrichum acutatum. Green and ripe fruits of cultivated Orange Kinkan were collected from a rural unit in Rio Verde, Goiás, Brazil. Additionally, the essential oil yield was determined by hydrodistillation in Clevenger-type apparatus. We observed essential oil yields of 3.57 and 3.64% to green and ripe fruits. Within the essential oils, we detected six major compounds β-pinene, limonene, β-felandrene, α-guaiene, germacrene D, and bicyclosesquifellandrene. Essential oils showed high inhibition percentage efficiency against the three fungal pathogens. Therefore, the essential oils of the green and ripe fruits of orange Kinkan may have antifungal applications.